High‐Resolution Pixelated Light Emitting Diodes Based on Electrohydrodynamic Printing and Coffee‐Ring‐Free Quantum Dot Film. Issue 10 (23rd July 2020) - Li, Hegeng; Duan, Yongqing; Shao, Zhilong; Zhang, Guannan; Li, Huayang; Huang, YongAn; Yin, Zhouping
Abstract: Inkjet printing for preparing quantum dot light emitting diodes (QLEDs) has become increasingly attractive due to its large‐area, low‐cost fabrication features. However, the rather low resolution and coarse morphology induced by the printing and uneven evaporation of droplet restrict its further development. Herein, electrohydrodynamic (EHD) printing and mixed solvent method are employed to fabricate high‐resolution pixelated QLEDs. By optimizing the mixed solvent ratio to weaken capillary flow, coffee‐ring‐free quantum dot (QD) films can be obtained. With the help of EHD printing process optimization and pixel defining layers introduction, high‐resolution pixelated QLED with 306 pixels per in. is achieved, which can meet the requirements of manufacturing mobile phones. Finally, an inverted pixelated QLED with a low turn‐on voltage of 3 V and a maximum luminance of 8533 cd m −2 is fabricated, demonstrating that the presented strategy has huge potential in high‐resolution and high‐quality QD display manufacturing. Abstract : To satisfy the resolution and film morphology requirements for pixelated quantum dot light emitting diodes (QLEDs), electrohydrodynamic printing (EHD printing) combined with mixed solvent method are presented to realize coffee‐ring‐free pixelated QLEDs with 306 pixels per inch (PPI). The device with high‐resolution and high‐brightness demonstrates their great potential in QLEDs device manufacturing.